A New SYBR Green qRT-PCR Diagnostic Method for Screening MCRV-Free Breeding Mud Crabs - Xu CHU; Wenhong FANG; Zhiqiang LIU; Junfang ZHOU; Xinshu LI; Xincang LI (Progress in Fishery Sciences, 2023)
Mud crab reovirus (MCRV) is one of the most fatal pathogens of the mud crab Scylla paramamonsain. The outbreak and epidemic of MCRV has seriously affected the healthy development of the mud crab aquaculture industry. To limit MCRV transmission from breeding crabs to larva, we attempt to establish a more sensitive and practical diagnostic method for screening MCRV-free crabs. The primers of the present diagnostic methods for MCRV are based on the VP1 gene (MCRV RNA polymerase gene), and the low expression level of this gene limits the sensitivity of the diagnostic method. Therefore, it is necessary to select the target gene with the highest expression level for the detection primer to improve the sensitivity of the diagnostic method. In addition, the current diagnostic methods require gill samples for virus detection, which requires killing the mud crabs before sampling. This sampling method is obviously not suitable for screening MCRV-free breeding crabs. Therefore, it is necessary to develop a less invasive sampling method for breeding crabs. In this study, a SYBR Green fluorescent quantitative diagnostic method was developed to screen MCRV-free breeding crabs. To improve the sensitivity of the detection, we initially analyzed the relative load of MCRV in the main tissues of infected mud crabs. The viral load in the hemolymph was the highest of all the tissues. The expression levels of 13 putative genes of MCRV were detected in the hemolymph. The relative expression level of the VP11 gene was the highest. Finally, specific primers were designed based on the conserved region of the VP11 gene sequence to establish a SYBR Green qRT-PCR (quantitative reverse-transcription PCR) detection method to accurately detect 50 copies/µL of viral nucleic acid in a sample. Considering the advantages of tissue and target gene selection, the sensitivity of this method should be significantly higher than that of preexisting detection methods. This diagnostic method is very specific for MCRV and no specific amplification was observed using nucleic acid samples containing 5 different kinds of common crustacean pathogens (MCDV, WSSV, DIV1, EHP, and Vibrio parahemolyticus). Compared to other methods of extracting RNA by killing and grinding the gill tissues of crabs, we can select MCRV-free crabs by sampling very small amounts of hemolymph (as low as 20 µL). All of the healthy crabs screened by this method were able to hold eggs that hatched normally. To test the effectiveness of this method, 22 breeding crabs and 20 commercial crabs were screened for MCRV. The positive rates were 54.55% and 85.00%, respectively. In addition, we analyzed the proliferation of MCRV in the mud crabs, and found that MCRV proliferates exponentially in the early stage, then enters a plateau phase, and no crabs died during the infection period of seven days. In conclusion, this study established a highly-sensitive and practical detection method for MCRV in breeding crabs, which can meet the requirements for MCRV-free breeding crab screening with low damage to the breeders. We also investigated the pathogenic infection mechanisms.